Metodología Para La Evaluación De Los Modelos De Gestión De Empendimientos Turisticos: Su Aplicación En El Cantón Puerto Francisco De Orellana – Ecuador - Vásconez, Rita Sulema Lara; Quinchuela, Flor; Muñoz, Eduardo (European Scientific Journal, ESJ, 2016)
The present investigation is carried out in the nature of an evaluation of the impact of models of management, taking them as the central point of reference to communal tourism, with emphasis on developing a simple direct methodology, which is permitted within the limits of the information gathered and available, to construct something consistent with the inherent concerns and the impacts on the model of management of communal tourism in the county of Puerto Francisco de Orellana. Furthermore, in addition there is a “ranking” among the businesses based on the studied dimensions and the information about the businesses: Napo Wild life Center, San Warmi, Association Pusarra, and the Community Shuar Atahualpa and the studied dimensions in each case, that is: associativity, appropriateness of actions, structures of the costs of the businesses, and finally, environmental effects in order to know if these contribute to determining if the initiatives of communal tourism determine the level of improvement of the conditions of the life of their founders.